Down‐regulation of the glucan synthase‐like 6 gene (HvGsl6) in barley leads to decreased callose accumulation and increased cell wall penetration by Blumeria graminis f. sp. hordei. Issue 2 (1st July 2016) - Chowdhury, Jamil; Schober, Michael S.; Shirley, Neil J.; Singh, Rohan R.; Jacobs, Andrew K.; Douchkov, Dimitar; Schweizer, Patrick; Fincher, Geoffrey B.; Burton, Rachel A.; Little, Alan
Summary: The recent characterization of the polysaccharide composition of papillae deposited at the barley cell wall during infection by the powdery mildew pathogen, Blumeria graminis f. sp. hordei ( Bgh ), has provided new targets for the generation of enhanced disease resistance. The role of callose in papilla‐based penetration resistance of crop species is largely unknown because the genes involved in the observed callose accumulation have not been identified unequivocally. We have employed both comparative and functional genomics approaches to identify the functional orthologue of AtGsl5 in the barley genome. HvGsl6 (the barley glucan synthase‐like 6 gene), which has the highest sequence identity to AtGsl5, is the only Bgh ‐induced gene among the HvGsl s examined in this study. Through double‐stranded RNA interference (dsRNAi)‐mediated silencing of HvGsl6, we have shown that the down‐regulation of HvGsl6 is associated with a lower accumulation of papillary and wound callose and a higher susceptibility to penetration of the papillae by Bgh, compared with control lines. The results indicate that the HvGsl6 gene is a functional orthologue of AtGsl5 and is involved in papillary callose accumulation in barley. The increased susceptibility of HvGsl6 dsRNAi transgenic lines to infection indicates that callose positively contributes to the barley fungal penetration resistance mechanism. Abstract : See also the Commentary on this article by Voigt, 212: 303–305 .